PEMBERDAYAAN PELATIH DAN ANGGOTA DALAM MEMBANGUN EKOSISTEM OLAHRAGA BERBASIS LITERASI KESEHATAN MENTAL PADA ORKI (OLAHRAGA KEBUGARAN INDONESIA) KOTA TANGERANG SELATAN - Dede Andi; Melda Wiguna; Siska Yunanti (Abdi Jurnal Publikasi, 2026)
This community service activity aims to enhance mental health literacy among coaches and members of ORKI (Olahraga Kebugaran Indonesia) in South Tangerang City and to promote the development of a sports ecosystem that is healthy both physically and psychologically. The main issues addressed include limited understanding of mental health, insufficient empowerment strategies, and the absence of a systematic approach to creating a supportive sporting environment.The methods employed in this program utilize a participatory approach based on educational activities and interactive training. The program began with the delivery of material on the importance of mental health in the sports domain, followed by simulations of stress-management techniques, case-based group discussions, empathic communication practice, and a Forum Group Discussion (FGD) aimed at formulating community strategies. Data were collected through direct observation, discussion outputs, and participant reflections.The results indicate an improvement in participants’ understanding of mental health issues, accompanied by emerging initiatives to establish internal support systems within ORKI. Coaches and members demonstrated positive changes in mindset and behavior, particularly in communication practices, training activity design, and responsiveness to the emotional conditions of fellow members. Thus, this program provides a significant contribution to empowering the sports community through an applicable and sustainable mental health literacy approach.